2017
DOI: 10.1186/s41182-017-0054-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors associated with the distribution of visceral leishmaniasis in endemic areas of Bangladesh: modeling the ecological niche

Abstract: BackgroundVisceral leishmaniasis (VL) is a parasitic infection (also called kala-azar in South Asia) caused by Leishmania donovani that is a considerable threat to public health in the Indian subcontinent, including densely populated Bangladesh. The disease seriously affects the poorest subset of the population in the subcontinent. Despite the fact that the incidence of VL results in significant morbidity and mortality, its environmental determinants are relatively poorly understood, especially in Bangladesh. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 91 publications
3
28
0
4
Order By: Relevance
“…Climatic changes in rainfall, humidity and atmospheric temperature influence behavioral activities and the life-cycle of vectors and reservoir hosts for leishmaniasis [35, 36]. A study in India reported that 29 °C to 31 °C was the most favorable range of the distribution of leishmaniasis, suggesting the potential of P. argentipes abundance in higher temperatures [37]. In the present study, we identified that all of the endemic regions are situated in low altitude areas less than 100 m above sea level and the mean temperature of all of these districts range between 26.5–28.5 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Climatic changes in rainfall, humidity and atmospheric temperature influence behavioral activities and the life-cycle of vectors and reservoir hosts for leishmaniasis [35, 36]. A study in India reported that 29 °C to 31 °C was the most favorable range of the distribution of leishmaniasis, suggesting the potential of P. argentipes abundance in higher temperatures [37]. In the present study, we identified that all of the endemic regions are situated in low altitude areas less than 100 m above sea level and the mean temperature of all of these districts range between 26.5–28.5 °C.…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of moist condition on the development of Ph. argentipes, the single proven vector of L. donovani in Bangladesh was assumed for the fact behind this evidence (Md Abdullah, Dewan, Shogib, Rahman, & Hossain, ). Also, precipitation in the driest months was effective on the distribution of ZVL in Sinking, northwest China (Gao & Cao, ).…”
Section: Discussionmentioning
confidence: 99%
“…Relation of ZVL with warmer seasons in Spain (Perez‐Cutillas et al, ), the maximum temperature of warmest months in Greece (Giannakopoulos et al, ), the maximum temperature of warmest quarter of year in China (Gao & Cao, ), land surface temperature in Bangladesh (Md Abdullah et al, ), higher range of temperature in India (Bhunia et al, ), mean annual temperature in Ethiopia (Tsegaw et al, ), the strong positive influence of temperature on dispersion of ZVL infected dog and vectors in Sao Paulo, Brazil (da Paixão Sevá, Mao, Galvis‐Ovallos, Lima, & Valle, ) and mean annual maximum daily temperature on vector of disease in Sudan (Thomson, Elnaiern, Ashford, & Connor, ) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Bununla birlikte, maksimum entropi (MaxEnt) içeren ekolojik niş modelleme, unsurların mevcut dağılım verilerine ihtiyaç duymaktadır. Kum sinekleri ve vektör kaynaklı hastalıkların dağılımının saptanmasında nitelikli tahmini işlevi ile bilinen yeni bir tekniktir (6,7). KL olası dağılımına etkili olduğu saptanan çevresel etmenlerden (BIO5, BIO9 ve BIO10) tümü hastalığın dağılımı ile doğru orantılı olduğu belirlenmiştir (Şekil 6a, 6b, 6c).…”
Section: Ozan Artun Hakan Kavurunclassified